Further Fertility Preservation Techniques - Dittrich, Ralf; von Wolff, Michael (Fertility Preservation in Oncological and Non-Oncological Diseases, 2020)
Cryopreservation of oocytes and ovarian tissue as well as the administration of GnRH agonists and transposition of the ovaries are well established as fertility preservation methods. In addition, there are alternative techniques that are less well established or still experimental. These techniques include medication to protect the ovaries, such as AS101, CIP and AMH, measures to use the ovarian tissue in patients with leukaemia and other diseases with a high risk of malignant cells in the ovarian tissue such as xenotransplantation, IVG and artificial ovaries, stem cells and uterus transplantation.
CRIS-Team Scopus Importer:2025-07-10
Keywords: Fertility preservation; FertiPROTEKT; Infertility; Ovarian tissue; Transplantation